2016
DOI: 10.4103/1817-1745.187625
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography morphometric analysis of the central clival depression and petroclival angle for application of the presigmoid approach in the pediatric population

Abstract: Aims:Lateral transtemporal approaches are useful for addressing lesions located ventral to the brainstem, especially when the pathologic diagnosis of the tumor dictates that a gross or near total resection improves outcomes. One approach, the presigmoid approach receives little attention in the pediatric population thus far. We sought to characterize morphometric changes, particularly the clival depth and the petroclival Cobb angle, that occur in the temporal bones of children and draw implications about doing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The petroclival angle appears to decrease (become less obtuse) in children less than 9 years of age, a favorable anatomic feature that allows for improved access via presigmoid retrolabyrinthine approaches to pathology in the central clival depression-the space between the internal acoustic meatus and the jugular tubercle, due to a shallower clival depression. 34 Complications common to these procedures in the adult population-cerebrospinal fluid (CSF) leakage, hearing loss, transient facial neuropathy-are seen in the pediatric population as well, a finding borne out by our previous institutional experience 1 as well as the report of Jackson et al, who reported on a series of 15 patients undergoing transtemporal approaches with the assistance of a neuro-otologist. 35 The role of an experienced neuro-otologist is of particular importance in children because the mastoid air cells are less well developed, which make identification of the facial nerve and bony labyrinth more difficult 36 (►Fig.…”
Section: Transtemporal Proceduresmentioning
confidence: 93%
“…The petroclival angle appears to decrease (become less obtuse) in children less than 9 years of age, a favorable anatomic feature that allows for improved access via presigmoid retrolabyrinthine approaches to pathology in the central clival depression-the space between the internal acoustic meatus and the jugular tubercle, due to a shallower clival depression. 34 Complications common to these procedures in the adult population-cerebrospinal fluid (CSF) leakage, hearing loss, transient facial neuropathy-are seen in the pediatric population as well, a finding borne out by our previous institutional experience 1 as well as the report of Jackson et al, who reported on a series of 15 patients undergoing transtemporal approaches with the assistance of a neuro-otologist. 35 The role of an experienced neuro-otologist is of particular importance in children because the mastoid air cells are less well developed, which make identification of the facial nerve and bony labyrinth more difficult 36 (►Fig.…”
Section: Transtemporal Proceduresmentioning
confidence: 93%
“…Some authors attempted to quantify the anatomical variability of certain aspects of the petroclival region, but these studies not only had small sample sizes but also measured a limited number of petroclival region anatomic parameters, [2][3][4][5][6] thus failing to provide a more comprehensive set of data to evaluate different vectors of an approach. In our study, we found that PCAs correlated positively with each other at both levels (carotid canal and IAC).…”
Section: Discussionmentioning
confidence: 99%
“…1 Access to the petroclival region has been the focus of multiple reports on surgical approaches. [1][2][3][4][5] The existing algorithms for choosing skull base approaches put minimal emphasis on the variability of bony anatomy among patients and its effect on the adequacy of the different surgical corridors. In this study, we evaluated the existence of variability in the bony anatomy of the posterior fossa in adults.…”
Section: Introductionmentioning
confidence: 99%